Effect of grand multiparity on adverse maternal outcomes: A prospective cohort study - Dasa, Tamirat Tesfaye; Okunlola, Michael A.; Dessie, Yadeta (Frontiers in Public Health, 2022)
Background Grand multiparity remains a risk factor for a wide range of obstetric complications, especially in developing countries. Grand multiparity has been shown to increase the risks of medical and obstetric complications during pregnancies. However, in a research setting, the risk factors associated with adverse maternal outcomes have yet to be adequately investigated among grand multiparity. Furthermore, there is limited information that examines the effect of grand multiparity on pregnancy outcomes in Ethiopia through prospective follow-up design. Objective This study aimed to investigate the effect of grand multiparity on pregnancy outcomes in selected public hospitals in the Sidama Region State of Ethiopia. Methods A prospective cohort study design was employed on 837 pregnant women who were admitted for delivery in selected public hospitals from January 1 to August 31, 2021. The study subjects were recruited during admission for labor and delivery. Every woman who was admitted to labor wards was screened for eligibility. The exposed group in this cohort was grand multiparity, and the non-exposed group was multiparity. Data collection was started from the first contact after admission and follow-up to discharge for adverse maternal outcomes. The risk factors for adverse maternal outcomes in grand multiparity were investigated using multivariable Poisson regression analysis. The risk factor was reported as an adjusted risk ratio (ARR) with a 95% confidence interval (CI). When the P-value was <0.05, statistical significance was declared. Results The cohort's overall cumulative incidence of adverse maternal outcomes were 39.9% (95%CI: 36.6, 43.4%). Among exposed groups, the incidence of adverse maternal outcomes were 47.1% (95%CI: 41.0–53.2) and 36.3% (95% CI: 32.3–40.6) the multiparity. When compared to multiparous women, grand multiparity was associated with a greater risk of postpartum hemorrhage (ARR = 2.1; 95%CI:1.6–2.7) and malpresentation (ARR = 1.3; 95% CI: 1.01–1.7). Conclusions Pregnant women with grand multiparity have a higher incidence of adverse maternal outcomes. Grand multiparity increased the risk of adverse maternal outcomes such as postpartum bleeding and malpresentation. In low-resource settings, we recommend that community health education, the provision of accessible and effective contraceptive services, and increased awareness of the adverse maternal outcome among grand multiparity during pregnancy on obstetric performance should be prioritized. Also, trained health providers can effectively decrease the risk factor with good antenatal care and delivery.